What was Woodstock? - Holub, Joan (What was--?, 2016)
"On August 15, 1969, a music festival called 'Woodstock' transformed one small dairy farm in upstate New York into a gathering place for over 400,000 young music fans. Concert-goers, called 'hippies,' traveled from all over the country to see their favorite musicians perform. Famous artists like The Grateful Dead played day and night in a celebration of peace, love, and happiness. Although Woodstock lasted only three days, the spirit of the festival has defined a generation and become a symbol of the hippie life."--